ABUL HASAN MOVARDI’S PEDAGOGICAL IDEAS ABOUT NAFS GREED AND LUST - Egamberganova (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This article discusses the pedagogical views of Movardi’s works and his unique ideas about nafs, which is greed and lust. Also, his views reflect on the essential religious qualities of humanity and their significance in the world.